Nilai Ekonomi dan Kontribusi Hasil Hutan Bukan Kayu (HHBK) Terhadap Pendapatan Masyarakat Kampung Cikupa Desa Baru Ranji Kecamatan Merbau Mataram - Nova Adella; Raudhah Shalsabillah; Mellani Mellani; Intan Saputri; Okta Refki; Firli Fachrezi Yansyah; Alief Rakhman Setyanto (Hidroponik : Jurnal Ilmu Pertanian Dan Teknologi Dalam Ilmu Tanaman, 2024)
This study aims to assess the economic value and contribution of Non-Timber Forest Products (NTFP) to the income of the community in Kampung Cikupa, Desa Baru Ranji, Merbau Mataram Subdistrict, South Lampung. The population of this research consists of community members, with a total of 200 households. A sample of 36 respondents was selected using simple random sampling. Data were collected through interviews using a questionnaire. The data were analyzed quantitatively to determine the economic value of NTFP based on the market price of the products collected by the community. The research results show that the level of contribution of NTFPs to the livelihoods of the people of Cikupa Village is still very small and the use of NTFPs has not been fully optimized by the community.